Pathogens causing bovine mastitis in selected farms in Labis, Johor - S Efendi, Ayunarni (2016)
This study was conducted to determine the prevalence and bacteriological assessment of subclinical mastitis and antimicrobial resistance of bacterial isolates from dairy cows in selected farms in Labis, Johor. A total of 128 samples were collected from four farms and tested using California Mastitis Test (CMT). Thirty four (26.56%) milk samples were found to be positive and subsequently subjected to bacterial culture and identification. A total of seven bacteria species were successfully isolated from the samples. The most prevalent bacteria was Staphylococcus aureus (41.67%), followed by Staphylococcus intermedius (27.10%) and Streptococcus uberis (10.40%), Staphylococcus shleiferi (8.33%) and Aerococcusviridans 2 (8.33%). The other two bacteria are Corynebacteriumsp. and Chromobacterium sp.; both having 2.10% prevalence. In general, the antibiotic susceptibility test displayed variable susceptibility against tested antibiotics. Staphylococcus aureus showed highest resistance at 92.60%, 88.89%, 74.08%, 66.67% and 14.82% towards gentamycin, streptomycin, tetracyline, penicillin G and oxytetracycline respectively. Staphylococcus intermedius are 100% resistant against gentamycin, streptomycin, 84.62% against tetracycline, 54.85% against penicillin G and 30.77% against oxytetracycline. It was found that most of the isolated bacteria are sensitive towards oxytetracycline, therefore making the antibiotic the most effective among the five tested antibiotic. This study indicates the need for urgent and effective control measures to tackle the increase in prevalence of subclinical mastitis and their antimicrobial resistance in the study area.